Perception of climate change among smallholder potato producers in northern Peru - Rosmery Y. Ayala; Jegnes Benjamín Meléndez-Mori; Nixon Haro; Nuri Carito Vilca Valqui; Manuel Oliva-Cruz (Sustainable Environment, 2025)
Although potato cultivation is of great economic and social importance in Peruvian agriculture, little attention has been paid to the impact of climate change on production. This study aims to assess farmers’ perceptions of climate change and compare them with meteorological records. Data were collected in the districts of Conila and Trita (Amazonas) through interviews with 101 farmers. Random Forest machine learning was used to determine how farmers perceive various factors related to climate change, such as temperature, deforestation, droughts, and decreased potato production. The results of this study show that the perception of climate change and its impacts varies according to each district’s productive and environmental conditions. While in Conila, agriculture is considered the main factor responsible for the phenomenon, in Trita, livestock farming is considered more important. Likewise, the main concerns of farmers differ. In Conila, reduced rainfall and increased diseases affect production, while in Trita, the main concern lies in the alteration of the rainfall regime and the decrease in crop yields. Farmers’ perceptions of the change in climatic variables coincide with the time series information for the last 30 years. These results show the crop’s vulnerability, as the impact generated by climate change affects potato yields.